Answer:
Step-by-step explanation:
No
Answer: 26 years.
Step-by-step explanation:
Let x = current age of Louise (in years).
Then current age of James = x+6
Eight years from now, James's age = x+6+8= x+14
4 years ago, Louise's age = x-4
According to the question
x+14 = 4(x-4)
⇒ x+14 = 4x-16
⇒ 4x-x = 16+14
⇒ 3x = 30
⇒ x= 10 = current age of Louise (in years).
current age of James = 10+6 = 16 years
Sum of current ages = 16+10=26 years.
hence, the sum of the current ages is 26 years.
Answer:
I believe it is 5.25
Step-by-step explanation:
if you multiply 3 and 7 then divide by 4 you will get 1 fourth of 21 which is 5.25 !!
G^−m ÷ g^n
1st g^−m=1/g^m, hence g^−m ÷ g^n = (1/g^m) /(g^n)==> 1/(g^m)(g^(n)
==> 1/(g^m+n) or g^(-m-n)
Answer:20.571
Step-by-step explanation:
x:y = 21: 24=7:8
8x=7y
y=8x/7
When x=18
y=8*18/7
y=20.571